THE EFFECTIVENESS AND ACCOUNTABILITY OF ONLINE LEARNING ASSESSMENT DURING COVID-19’s MOVEMENT CONTROL ORDER: (A CASE OF KUPTM) - Mohd Zahrul Baharin; Soraya Sharifuddin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Teaching assessment is a significant foundation to be evaluated in higher education so as to distinguish improvement or any necessity needs in connection to teaching and learning quality. Since the implementation of MCO out of the impact of COVID-19, students learning session is severely impacted especially on the assessments. In-class assessments are no longer viable thus resulting the online assessments mode for all teachers and students. The purpose of this research is to study the effectiveness and accountability of online assessments in comparison with traditional assessments as well as to see the perception of students towards online learning during MCO. Data were collected using online questionnaire from respondents of higher learning institutions in Malaysia. The data were then analyzed using descriptive statistics using Statistical Package for Social Sciences (SPSS version 23.0.). The findings revealed low effectiveness and low accountability towards online assessments, but high perception towards online learning. The future scope of this study should be expanded to the type of assessments preferred by students during MCO and factors contributing to the effectiveness of online assessment.